Factor V Leiden and Prothrombin Gene G20210A Mutation in Children with Venous Thromboembolism - Bonduel, Mariana; Hepner, Mirta; Sciuccati, Gabriela; Pieroni, Graciela; Feliú-Torres, Aurora; Mardaraz, Claudia; Frontroth, Juan Pablo (Thrombosis and Haemostasis, 2002)
To determine whether factor V Leiden (FVL) and/or prothrombin gene G20210A mutation (PT20210A) are risk factors for venous thromboembolism (VTE) in Argentinean children. One hundred and thirty consecutive children with VTE were prospectively assisted at a single centre. Blood samples were available from 110 of them for detailed haematological analysis. The prevalence of both mutations was compared with a control group. The odds ratio for VTE was significantly increased in patients with FVL (OR 3.64; 95% CI: 1.14-11.6, p <0.029) whereas odds ratio for VTE was not significantly increased in patients with PT20210A (OR 1.06; 95% CI: 0.24-4.73, p = 0.938). Combined disorders were found in 5 of the 10 children with the aforementioned mutations. In 21 children (19%) without these mutations other inherited and acquired disorders were detected. Our data show that FVL is a risk factor for VTE whereas PT20210A does not seem to be a risk factor in our paediatric population.
Keywords: Venous thromboembolism; Factor V Leiden; prothrombin gene G20210A mutation; children; prothrombotic abnormalities